PENGEMBANGAN MEDIA ANIMASI BERBASIS MULTIPEL REPRESENTASI MATERI KELARUTAN DAN HASIL KALI KELARUTAN - Muhammad Zainul Arifin; Nina Kadaritna; Ila Rosilawati (Universitas Lampung, 2014)
This research aimed to develop animation media based on multiple representations about solubility and constant solubility product material. This research methods used